TEACHING SPEAKING TO A2 LEVEL LEARNERS THROUGH MIND MAPPING - Bekbergenova Gulayim Ayjarikovna; Tolibaeva Kamila Timurovna (TADQIQOTLAR, 2026)
Abstract: Teaching speaking to A2 level learners is a rewarding yet challenging task for educators. At this proficiency level, learners are developing their ability to communicate  basic  ideas,  express  opinions,  and  interact  in  simple  conversations. However,  they  may  still  lack  confidence,  have  limited  vocabulary,  and  encounter difficulties with fluency and organizing their thoughts. Mind mapping can serve as an effective tool to address these challenges and enhance the speaking skills of A2 level learners.  This  article  will  explore  the  benefits  of  mind  mapping  in  the  language classroom, provide practical strategies for implementation, and discuss the positive outcomes it brings to both students and teachers.